Impact Evaluation of Wastewater Treatment Based on the Anaerobic Digestion of Sewage Sludge Using the Life Cycle Assessment Method - Mohammad Rahmati; Majid Rasouli; Hossein Haji Agha Alizadeh; Behnam Ataeiyan (International Journal of Chemical Engineering)
All the inputs and outputs of a technical system can be interpreted from an environmental point of view. Using the life cycle assessment (LCA) approach, some changes that are less harmful to the environment can be included in the system. This research aims to evaluate the environmental effects of the wastewater treatment plant (WWTP) in South Tehran, and the LCA method was used in this study. Based on the data of qualitative parameters obtained from the measurement of Tehran province’s water and sewage company, the environmental emissions were calculated and analyzed using SimaPro software (9.0.0) and the standards defined under the ReCiPe 2016-midpoint method. In the ReCiPe 2016 method, the results were expressed in two intermediate levels (including three classes of influence) and final (including 18). The results showed that the treated wastewater and chlorine factors had the most adverse environmental effects. Among the 18 effect classes, the treated wastewater in the class of marine environmental toxicity with the amount of 101.1531 kg 1,4-DCB had the most environmental impacts among other classes. The power consumed by the biogas-burning combined heat and power (CHP) unit in the wastewater treatment (WWT) process reduced the environmental effects in most impact classes. The most adverse environmental effects of the WWT process are related to damage to human health and the ecosystem. According to the findings, the use of CHP systems is suggested for energy saving and also for reducing harmful effects on the environment.